Penerapan Model Problem Based Learning (PBL) dalam Meningkatkan Hasil Belajar IPAS di Kelas V SDN 16 Pulau Karam Kabupaten Pesisir Selatan - Wini Media Putri; Tiok Wijanarko (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
This study aims to describe the improvement of student learning outcomes in science learning using the Problem Based Learning (PBL) Model in Class V of SDN 16 Pulau Karam, Pesisir Selatan Regency. This study is a classroom action research (PTK) with a qualitative and quantitative approach. Implemented in 2 cycles, cycle I consists of 2 meetings and cycle II consists of 1 meeting. The results of the study showed an increase in teaching modules in science learning using the Problem Based Learning (PBL) model, the implementation of science learning using the Problem Based Learning (PBL) model and student learning outcomes in science learning using the Problem Based Learning (PBL) model. This can be seen from the average observation results of the Teaching Module cycle I which was 87.4% (B) increasing in cycle II to 92.8% (SB). This is also seen in the average results of teacher activities in cycle I which were 85.9% (B) increasing in cycle II to 93.8% (SB). In student activities, the average cycle I was 84.3% (B) increasing in cycle II to 93.8%. In student learning outcomes, the average cycle 1 was 81% (B) and increased in cycle 2 to 91%. Based on these results, it can be concluded that using the Problem Based Learning (PBL) model can improve the results of learning science in class V SDN 16 Pulau Karam, Pesisir Selatan Regency.